Carex hartmaniorum (Cyperaceae), a new species for the Spanish flora - Pérez Haase, Aaron; Jiménez-Mejías, Pedro; Andrieu, Frédéric; Richard, Léa; Lewin, Jean-Marc; Martín-Bravo, Santiago; Luceño, Modesto (Mediterranean Botany, 2024)
Carex hartmaniorum (sect. Racemosae, Cyperaceae) is reported for the first time for Spain, from a single known population in the Cerdanya region (Eastern Pyrenees, Girona province). The main differences with closely related taxa are highlighted, a dichotomous key to differentiate this species from members of section Racemosae inhabiting the Iberian Peninsula and the Pyrenees is presented, and some comments on its distribution and ecology are made. A preliminary conservation assessment for Spain resulted in the proposal of the Endangered category of C. hartmaniorum for Spain.